2013
DOI: 10.1111/tpj.12178
|View full text |Cite
|
Sign up to set email alerts
|

miR396 affects mycorrhization and root meristem activity in the legume Medicago truncatula

Abstract: These authors contributed equally to this work. SUMMARYThe root system is crucial for acquisition of resources from the soil. In legumes, the efficiency of mineral and water uptake by the roots may be reinforced due to establishment of symbiotic relationships with mycorrhizal fungi and interactions with soil rhizobia. Here, we investigated the role of miR396 in regulating the architecture of the root system and in symbiotic interactions in the model legume Medicago truncatula. Analyses with promoter-GUS fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(127 citation statements)
references
References 66 publications
0
127
0
Order By: Relevance
“…As indicated in the table below, the predicted targets for all of the abundant phasiRNAs belong to a wide variety of transposable elements. The lower table lists phasiRNAs that are abundant and target 10 or more encoding a long-chain fatty acid CoA ligase (Table 2), functions in ROS scavenging (Bazin et al, 2013). The activity of these miRNAs to trigger phasiRNAs is consistent with complex posttranscriptional regulation in nodule development.…”
Section: Discussionmentioning
confidence: 88%
“…As indicated in the table below, the predicted targets for all of the abundant phasiRNAs belong to a wide variety of transposable elements. The lower table lists phasiRNAs that are abundant and target 10 or more encoding a long-chain fatty acid CoA ligase (Table 2), functions in ROS scavenging (Bazin et al, 2013). The activity of these miRNAs to trigger phasiRNAs is consistent with complex posttranscriptional regulation in nodule development.…”
Section: Discussionmentioning
confidence: 88%
“…By contrast, miR172, miR396, miR5020, miR5629, miR5645, and miR5648 showed significant down-regulation in the 35S::SAP11 AYWB transgenic plants. Among them, miR2111, miR399, and miR827 have been shown to be up-regulated by Pi starvation (Hsieh et al, 2009;Pant et al, 2009), and miR399 and miR827 play important roles in regulating Pi homeostasis (Liu et al, 2012;Huang et al, 2013;Lin et al, 2013); miR160 and miR396 are required for regulating the auxin signaling response and cell proliferation during leaf and root development (Gutierrez et al, 2009;Pulido and Laufs, 2010;Debernardi et al, 2012;Bazin et al, 2013); miR172 has been shown to regulate the transition from the vegetative to reproductive phases (Aukerman and Sakai, 2003;Wu et al, 2009); and miR394 is required for the regulation of leaf morphology and shoot meristem stem-cell maintenance (Song et al, 2012;Knauer et al, 2013). However, miR5020b, miR5629, miR5639, miR5645d, miR5648, miR5655, and miR850 are newly identified miRNAs with unknown functions.…”
Section: Genome-wide Identification Of Differentially Expressed Mirnamentioning
confidence: 99%
“…Analysis of the correlations between modules and responses to symbiotic or pathogenic microbes showed that the cyan and green modules appeared to be respectively negatively or positively correlated to the response to S. meliloti infection (r = -0.85 and r = 0.64) whereas the orange module grouped miRNAs discriminating symbiotic and pathogenic responses (r = 0.91). Again, certain miRNAs already known to be involved in the regulation of symbiotic and pathogenic processes, such as miR169 variants [20], miR171h and other variants [22,23], miR393 [16], miR396 [15], sly-miR482* and miR2118 [19], were found, suggesting coregulatory roles for the newly discovered miRNAs present in those modules. Interestingly, analysis of the enrichment of GO terms on target mRNAs (Additional file 6: Figure S9b), showed that miRNAs of the orange module (discriminating symbiotic and pathogenic responses) mainly target genes involved in defense response, proteolysis and nodule morphogenesis (23%, 23% and 12%, respectively).…”
Section: Symbiotic Myc and Nod Signals Reveal Early Activation Of Mirmentioning
confidence: 99%
“…In legumes, a role of miR399 in responses to increased phosphate, a nutritional status linked to effective mycorrhization, was reported by Branscheid et al [12]. Other miRNAs, like miR164, miR166 or miR396, were shown to play indirect roles in nodule development or mycorrhizal symbiosis due to their global impact on auxin responses and/or tissue patterning in roots [13][14][15]. Concerning plant-pathogen interactions, miRNAs linked to auxin signaling were related to defense reactions in A. thaliana [16,17] and more recent studies provided evidence that some miRNAs function as master regulators of diseaseresistance genes encoding nucleotide-binding site leucinerich repeat (NBS-LRR) proteins in diverse plants [18,19].…”
Section: Introductionmentioning
confidence: 98%